Cost-Benefit Analysis of Vaccination Strategies to Prevent Mother-to-Child Transmission of the Hepatitis B Virus Using a Markov Model Decision Tree - Yang, Nan; Lei, Lei; Meng, Yiyu; Zhou, Naitong; Shi, Lizheng; Hu, Ming (Frontiers in Public Health, 2022)
Objectives: Several strategies for preventing mother-to-child transmission (MTCT) of the Hepatitis B virus (HBV) were composed of HBV vaccination and hepatitis B immunoglobulin (HBIG) with different routes of administration and dosages. The aim of this study is to evaluate the economic viability of the current hepatitis-B vaccination strategies for preventing MTCT from a societal perspective to optimize the current immunization strategy for preventing MTCT of the HBV, and offer ideas for national health administration in China. Method: To simulate the disease outcome for the entire life of newborns infected with the HBV, a Markov model with eight possible health states was built by using TreeAge Pro 2011 software. The parameters of the model in the present study were probability and cost, which were extracted from literature and calculated by Microsoft Excel 2013. The optimal immunization strategies were selected through cost-benefit analyses. Benefit-cost ratio >1 indicated that the strategy had positive benefits, and vice versa. One-Way Sensitivity Analyses was used to investigate the stability of results. Results: From a societal perspective, we evaluated the economic viability of 11 strategies in China. For all 11 strategies, the BCR＞1: the benefits of all strategies were greater than the costs. We recommended strategy number 9 as being optimal in China. In strategy number 9, babies born to HBsAg-positive mothers should be given a HBIG (200 IU) within 24 hours of birth, and three injections of the hepatitis-B vaccine (20-μg each) at 0, 1, 6 months, and the BRC = 4.61. One-way sensitivity analyses revealed that the full vaccination coverage and effective rates of protection of different prevention strategies had a great influence on the BCR, whereas other factors had little effect. Conclusions: The benefits of all strategies were greater than the costs. For decision-making and application, the strategy should be based on the social and economic conditions of different regions so that an appropriate immunization strategy can be selected.